BRCA1-like profile predicts benefit of tandem high dose epirubicin-cyclophospamide-thiotepa in high risk breast cancer patients randomized in the WSG-AM01 trial - Schouten, Philip; Gluz, Oleg; Harbeck, Nadia; Mohrmann, Svjetlana; Diallo‐Danebrock, Raihana; Pelz, Enrico; Kruizinga, Janneke; Velds, Arno; Nieuwland, Marja; Kerkhoven, Ron M.; Liedtke, Cornelia; Frick, Markus; et al. (International journal of cancer, 2016)
BRCA1 is an important protein in the repair of DNA double strand breaks (DSBs), which are induced by alkylating chemotherapy. A BRCA1-like DNA copy number signature derived from tumors with a BRCA1 mutation is indicative for impaired BRCA1 function and associated with good outcome after high dose (HD) and tandem HD DSB inducing chemotherapy. We investigated whether BRCA1-like status was a predictive biomarker in the WSG AM 01 trial. WSG AM 01 randomized high-risk breast cancer patients to induction (2× epirubicin-cyclophosphamide) followed by tandem HD chemotherapy with epirubicin, cyclophosphamide and thiotepa versus dose dense chemotherapy (4× epirubicin-cyclophospamide followed by 3× cyclophosphamide-methotrexate-5-fluorouracil).